2012
DOI: 10.5194/nhess-12-2299-2012
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception – issues for flood management in Europe

Abstract: Abstract. Public perception of flood risk and flood risk information is often overlooked when developing flood risk management plans. As scientists and the public at large perceive risk in very different ways, flood risk management strategies are known to have failed in the past due to this disconnect between authorities and the public. This paper uses a novel approach in exploring the role of public perception in developing flood risk communication strategies in Europe. Results are presented of extensive quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
262
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(284 citation statements)
references
References 43 publications
15
262
1
6
Order By: Relevance
“…Low levels of preparedness are related to information, which is a clear driver that determines the effectiveness of non-structural mitigation measures at large (Lindell et al, 2007). The relationship between knowledge of evacuation routes and levels of preparedness revealed by our results can be compared with similar evidence, associated with high levels of worry, obtained by Bradford et al (2012), who interviewed people in Belgium, Finland, Germany, Ireland and Italy (n = 1231). Regarding information and preparedness, their research had similar results to ours, as only 34 % of their participants considered themselves prepared for future floods.…”
Section: Context Information and Experiencesupporting
confidence: 74%
“…Low levels of preparedness are related to information, which is a clear driver that determines the effectiveness of non-structural mitigation measures at large (Lindell et al, 2007). The relationship between knowledge of evacuation routes and levels of preparedness revealed by our results can be compared with similar evidence, associated with high levels of worry, obtained by Bradford et al (2012), who interviewed people in Belgium, Finland, Germany, Ireland and Italy (n = 1231). Regarding information and preparedness, their research had similar results to ours, as only 34 % of their participants considered themselves prepared for future floods.…”
Section: Context Information and Experiencesupporting
confidence: 74%
“…In any case, this appears to be an incentive to inform residents living in flood-prone areas about how to protect their property against floods. The same notion has also been presented in other studies [1,2]. However, landowners were more interested in insurance.…”
Section: Discussionsupporting
confidence: 54%
“…1,2] have suggested that massive flood protection constructions are not sustainable solutions in the long term. Instead, greater emphasis should be placed on flood mitigation measures implemented by private households.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore one possible implication of these results is that it is not so much important to improve communication about risk perception and concern per se: it is equally important to improve the communication about how citizens should behave in case of flood. The URFlood addressed this more in detail, by giving guidelines on ways to improve flood risk communication in order to address local behaviours and to increase the resiliency of the affected communities (Bonaiuto et al, 2011;Bradford et al, 2012;O'Sullivan et al, 2012). Indeed, according to and consistent with the abovementioned results, for a flood risk communication to be effective it is fundamental to improve awareness about the current flood information sources among the citizens at risk, and to develop clearer and more understandable statements on flood risk.…”
Section: Dvsmentioning
confidence: 99%